2004
DOI: 10.1128/aem.70.9.5244-5251.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of CcpA and Involvement of This Protein in Transcriptional Regulation of Lactate Dehydrogenase and Pyruvate Formate-Lyase in the Ruminal Bacterium Streptococcus bovis

Abstract: A ccpA gene that encodes global catabolite control protein A (CcpA) in Streptococcus bovis was identified and characterized, and the involvement of CcpA in transcriptional control of a gene (ldh) encoding lactate dehydrogenase (LDH) and a gene (pfl) encoding pyruvate formate-lyase (PFL) was examined. The ccpA gene was shown to be transcribed as a monocistronic operon. A catabolite-responsive element (cre) was found in the promoter region of ccpA, suggesting that ccpA transcription in S. bovis is autogenously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
6
31
0
Order By: Relevance
“…In anaerobic conditions and in the presence of slowly fermentable sugars, PFL is responsible for the shift from homolactic to mixed-acid fermentation in L. lactis (3,25). In S. bovis, it was shown that pfl expression is also dependent on the nature of the fermentable carbon source via a CcpA-dependent mechanism (4,9). In the strain LMG18311, a catabolite-responsive element (cre box) was detected upstream of pfl (sequence TGTAAGCGGTTACT, at Ϫ92 bp upstream of the putative ATG start codon), suggesting that the nature of the carbon source would also modulate pfl expression in S. thermophilus.…”
Section: Discussionmentioning
confidence: 99%
“…In anaerobic conditions and in the presence of slowly fermentable sugars, PFL is responsible for the shift from homolactic to mixed-acid fermentation in L. lactis (3,25). In S. bovis, it was shown that pfl expression is also dependent on the nature of the fermentable carbon source via a CcpA-dependent mechanism (4,9). In the strain LMG18311, a catabolite-responsive element (cre box) was detected upstream of pfl (sequence TGTAAGCGGTTACT, at Ϫ92 bp upstream of the putative ATG start codon), suggesting that the nature of the carbon source would also modulate pfl expression in S. thermophilus.…”
Section: Discussionmentioning
confidence: 99%
“…CcpA has also been identified to function in the regulation of catabolic operons and catabolite repression in many Streptococcus spp. (1,17,59,77). CcpA has also shown to be required for biofilm formation in Streptococcus mutans (80).…”
mentioning
confidence: 99%
“…This interaction increases the affinity of CcpA for the cre. Binding of this dimeric complex typically causes repression of promoters, facilitating CCR (1,13,14). CcpA residues involved in binding of Pϳ Ser-HPr (38) and those involved in binding of cre (37) have been characterized, and the crystal structure of the CcpA-Pϳ Ser-HPr complex has been recently solved (63).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When present, the pneumococcus modifies gene expression to ensure the prioritized usage of these sugars through a process called carbon catabolite repression (CCR). Pertinent to this article, glucose-mediated CCR results in the conversion of pyruvate to lactate, using the enzyme lactate dehydrogenase (24). Whereas in the absence of glucose and growth in galactose, pyruvate is converted to acetyl phosphate using the enzyme pyruvate oxidase (Fig.…”
mentioning
confidence: 99%